TaLNA App: An Interactive Numeracy Mobile Learning Application for Children with Autism - Kamaruzaman, Muhamad Fairus; Abdul Majid, Faizah; Mujio Mukmin, Toto (International Journal of Interactive Mobile Technologies (iJIM), 2023)
In light of the COVID-19 pandemic’s disruptions to education, there is a growing need for alternative learning methods, particularly for children with autism who thrive on routine and familiarity. This study aims to enhance numeracy learning for children with autism by using the touchscreen-assistive learning numeracy application (TaLNA) during the post-pandemic period, aligning with Sustainable Development Goal (SDG) 4 (quality education). Our primary focus is to leverage mobile learning through the TaLNA application to provide specialized educational content and remote progress monitoring. Combining mobile learning with SDG 4 principles ensures continuous access to education, promoting inclusivity and equity, even in challenging circumstances. Mobile learning offers personalized numeracy experiences tailored to individual needs, maintaining educational consistency and structure amidst disrupted routines and environments. This research has significant implications for instructors, teachers, and parents of children with autism, providing valuable insights for their pedagogical approaches.